Anthropogenic PMx air pollution susceptibility using AHP method in Java Island, Indonesia - Nugraha, Hasan Adi; Ragita, Putri; Kurniawan, Bayu; Raihan, Hana Syafi; Aisy, Yumna Rohadatul; Sawitri, Indah; Alverina, Clara; Prasetya, Bagus Dwi; Styawan, Nirmala Hasna; Putri Gunawan, Ananda Shabrina; Krisanto, Emanuel Tatag; Putri, Ratih Fitria; et al. (EDP Sciences, 2023)
Various health and welfare problems in human society originate from air pollution. PMx as one of the hydrometeorological hazards caused by humans is sustainable, ironically having an impact on the lives of human society, especially in areas that are densely populated. This research aims to estimate the susceptibility of PMx air pollution in Java Island, Indonesia. This island was chosen because it has a large population (151.59 million people in 2020) and is growing into a regional economic and industrial center. Java Island also has various cases of extreme air pollution. In this study, the Analytical Hierarchy Process (AHP) method is utilized to assess the susceptibility of anthropogenic PMx air pollution, taking into account factors like morphology, rainfall, mining area buffers, industrial area buffers, and traffic buffers. The results showed that anthropogenic PMx susceptibility was related to active and passive factors. The active factor is anthropogenic activity, while the passive factor is natural inhibition. Anthropogenic activities that have a big influence are industrial activities, followed by mining activities, and transportation. Meanwhile natural inhibitors such as rainfall and morphology, have a relatively smaller influence. Analysis of susceptibility distribution is very important for mitigating air pollution hazards, especially in Java Island. © 2023 EDP Sciences. All rights reserved.